The effect of defect size on mortality and morbidity in patients with neural tube defect (Annals of Medical Research, 2022)
Aim: Neural tube defects (NTD) occur due to errors in the closing of neural canal in embryo. All over the world, the incidence of all forms of NTD varies between 1.4 and 2 in every 1000 live births. The aim of the present study was to investigate the short term prognosis, accompanying anomalies and complications in patients with NTD and to evaluate the relation between defect sizes. Material and Methods: Patients who applied to Inonu University Neonatology Department between January 2010 and December 2017 with the diagnosis of NTD and were operated on were included in the study. Babies who died within the first 24 hours were excluded from the study. Patients were divided into two groups according to the size of NTD; < 5 cm (Group 1) and ≥ 5 cm (Group 2). Approval for the study was obtained from local ethics committee. Results: Overall 133 infants were included in the study. Mean birth weight was 3155 ± 531 g and mean duration of pregnancy was on 38.1 ± 1.8 weeks. Of NTD’s 82% was located in lumbosacral region. 90.2% of the patients underwent operation within the first 24 hours. Parameters such as hydrocephalus, need for shunt, need for flap in tissue defects, the rate of postoperative complications, duration of hospitalization, mortality and the use of antibiotics were found to be at a higher rate in cases whose defect size was ≥5 cm than in those whose defect size was < 5 cm (p < 0.005). Postoperative complications developed in 48.1% of the patients. The most common complications were observed to be cerebrospinal fluid (CSF) leakage (24.1%) and bladder dysfunction (7.5%). Conclusion: In patients with NTD, as the size of the defect increases, additional interventions, complications, hospitalization rates and mortality increase as well. Therefore, it is recommended that health care personnel should take care against problems in the management of this group of patients and inform familes beforehand on these issues.
Keywords: Defect size; neural tube defect; newborn; meningomyeloceleddd